PENINGKATAN PEMAHAMAN KONSEP IPAS KELAS V MELALUI MODEL PjBL MENGGUNAKAN MEDIA VISUAL - Fadholi, Ahmad; Fakhriyah, Fina; Fathonah, Nurul (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Meaningful education in schools is education that is implemented effectively, namely students learn actively and are actively involved-participatively to build their knowledge. One effective way to increase active involvement of students is to apply the Project Based Learning (PjBL) learning model. The low understanding of the concept of the subject of science and supported by the presentation of material in the student's worksheet book that is less interesting is the cause of learning difficulties for students. This research was conducted at SD NU Nawa Kartika Kudus class V B, subject of science and natural resources, Indonesia's rich biodiversity and nature with the PjBL learning model with visual media. This research model uses PTK (Classroom Action Research) with data analysis procedures according to the opinions of Miles and Huberman and descriptive statistical data analysis. The results of this study showed an increase in the average results of student assessments of 44.9 (percentage 5.6%) from the pre-cycle, then the average student assessment of 62.4 (percentage 30.6%) from cycle 1, and the average student assessment of 81.5 (percentage 91.7%) in cycle 2. Based on the results of the study, there was a significant and positive increase in understanding of the concept of IPAS because from each learning or research process from the pre-cycle, cycle 1, and up to cycle 2 there was always an increase.